2010
DOI: 10.1016/j.pain.2010.08.007
|View full text |Cite
|
Sign up to set email alerts
|

How the number of learning trials affects placebo and nocebo responses

Abstract: Conditioning procedures are used in many placebo studies because evidence suggests that conditioning-related placebo responses are usually more robust than those induced by verbal suggestions alone. However, it has not been shown whether there is a causal relation between the number of conditioning trials and the resistance to extinction of placebo and nocebo responses. Here we test the effects of either one or four sessions of conditioning on the modulation of both non-painful and painful stimuli delivered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
238
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(269 citation statements)
references
References 48 publications
25
238
1
5
Order By: Relevance
“…Previous studies have shown that a single learning trial is sufficient to induce both nocebo and placebo responses, but as learning trials increase, the more persistent the effects of the manipulation become (Colloca et al 2010). Thus, the present results are consistent with previous studies suggesting that verbal suggestions efficiently induce nocebo responses Aslaksen & Lyby 2015), while placebo responses might require a more robust pain relief experience (Schenk et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that a single learning trial is sufficient to induce both nocebo and placebo responses, but as learning trials increase, the more persistent the effects of the manipulation become (Colloca et al 2010). Thus, the present results are consistent with previous studies suggesting that verbal suggestions efficiently induce nocebo responses Aslaksen & Lyby 2015), while placebo responses might require a more robust pain relief experience (Schenk et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The few studies that do exist suggest that nocebo hyperalgesia is caused by expectations of pain increase that induce negative emotions, which in turn increase pain. Furthermore, only a few studies have compared nocebo hyperalgesia and placebo analgesia in the same design (Colloca et al 2010;Reicherts et al 2016). Nocebo hyperalgesia can be reversed by anxiolytic drugs (Benedetti et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, pain can be reduced by distraction (Valet et al, 2004;Buhle and Wager, 2010;Sprenger et al, 2012), expectation (Koyama et al, 2005;Atlas et al, 2010), or in general by placebo interventions (Levine et al, 1978;Montgomery and Kirsch, 1996;Amanzio and Benedetti, 1999;Benedetti, 2008). On the other hand, pain can be increased by negative expectations, for example in nocebo hyperalgesia (Lorenz et al, 2005;Colloca et al, 2008). In some studies, negative expectations even equalized the effects of analgesic drugs (Dworkin et al, 1983;Bingel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that placebo and nocebo responses rely on different neurobiological mechanisms (Colloca et al, 2008;Enck et al, 2008;Petrovic, 2008), which could mean that only placebo analgesia affects spinal pain transmission. To test the hypothesis of a spinal cord involvement in nocebo hyperalgesia, we used novel functional magnetic resonance imaging (fMRI) acquisition techniques, allowing for the investigation of pain transmission in the human spinal cord (Eippert et al, 2009b;Cahill and Stroman, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of clinical and experimental studies have clearly shown that placebos can indeed affect symptomatology, as demonstrated, for example in patients with depression [1,2], Parkinson's disease [3 -6], pain [7,8] and asthma [9]. How is it that substances without any defined active component affect not only psychological but more importantly physiological functions?…”
Section: Introductionmentioning
confidence: 99%